Glioblastoma as an age-related neurological disorder in adults. Issue 1 (4th September 2021) - Kim, Miri; Ladomersky, Erik; Mozny, Andreas; Kocherginsky, Masha; O'Shea, Kaitlyn; Reinstein, Zachary Z; Zhai, Lijie; Bell, April; Lauing, Kristen L; Bollu, Lakshmi; Rabin, Erik; Dixit, Karan; et al.
Abstract: Background: Advanced age is a major risk factor for the development of many diseases including those affecting the central nervous system. Wild-type isocitrate dehydrogenase glioblastoma (IDH wt GBM) is the most common primary malignant brain cancer and accounts for ≥90% of all adult GBM diagnoses. Patients with IDH wt GBM have a median age of diagnosis at 68–70 years of age, and increasing age is associated with an increasingly worse prognosis for patients with this type of GBM. Methods: The Surveillance, Epidemiology, and End Results, The Cancer Genome Atlas, and the Chinese Glioma Genome Atlas databases were analyzed for mortality indices. Meta-analysis of 80 clinical trials was evaluated for log hazard ratio for aging to tumor survivorship. Results: Despite significant advances in the understanding of intratumoral genetic alterations, molecular characteristics of tumor microenvironments, and relationships between tumor molecular characteristics and the use of targeted therapeutics, life expectancy for older adults with GBM has yet to improve. Conclusions: Based upon the results of our analysis, we propose that age-dependent factors that are yet to be fully elucidated, contribute to IDH wt GBM patient outcomes.